EVALUASI INOVASI SISTEM PELAYANAN PUBLIK PROVINSI SUMBAR UNTUK MENGHADAPI NEW NORMAL - Emi Handrina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: The urge to use technology in governance has been increasing since e-governance was used. This is confirmed by the emergence of the idea of the Industrial Revolution 4.0 recently. The government is required to be adaptive and able to optimize technology in serving the community. Not to mention in the midst of the Covid-19 pandemic, which forces people to limit their mobility and are advised to do activities from home to stop the spread of the virus. In this condition, the presence of government services must immediately transform into online form. The application of technology in public services today is basically not a new thing. The Regional Government as a government that is in direct contact with the community is already a public service through applications and online systems. As in the process of managing population documents, one of them is in West Sumatra. However, the application of technology in public services is still not optimal so that its implementation is not in accordance with new normal conditions. This research was conducted using a literature study method with descriptive analysis. From the literature study, it was found that one method to optimize the public service process is e-governance infrastructure in the form of an integrated online public service system from the government for the provision of information and public services. The results of this study can be a relevant source for policy makers for ASN in Indonesia by providing recommendations so that e-government schemes can be implemented so as to provide easy access for the community and increase work effectiveness and ASN safety in order to face the new normal period.Keywords: Public Service, E-Governance, Covid-19, West Sumatra